Religion, culture, society: readings in the humanities and revealed knowledge - Quayum, Mohammad Abdul (Silverfish Books Sdn. Bhd., 2017)
This book contains eleven articles by lecturers from the Kulliyah of Islamic Revealed Knowledge and Human Science,s International Islamic University Malaysia (IIUM). For those not familiar with the University's nomenclature, "Kulliyah" is an Arabic word that means "college" or "faculty." The Kulliyah of Islamic Revealed Knowledge and Human Science is the largest faculty in the University, comprising eleven departments - four in Islamic Revealed Knowledge (or Islamic Studies) and seven in Human Sciences (or Humanities and Social Sciences). One might wonder why so many departments and with such diverse interests have been clustered into a single faculty in a traditional university, obviously Islamic studies would form a faculty by itself, while Humanities and Social studies would either be combined or given separate academic and administrative identities. But the founders of International Islamic University Malaysia defined this institution with one overarching tenet in mind: 'Islam."